Cystic Fibrosis: Review - I Gusti Agung Ari Kusuma Yana (Jurnal Sains dan Kesehatan, 2021)
Cystic fibrosis (CF) is a reversed autosomal genetic disease that originates from some white or caucasian races. This condition is caused by mutations in the CFTR gene, especially the CFTR Phe508del. If CFTR damage or error occurs then normal function will be disrupted and have a clinical impact on other organs or multiorgan. Complications such as the pancreas, liver, digestive tract, bone, genital, and respiratory tract that can cause most deaths in patients with cystic fibrosis. Malabsorption, inflammation, infection and lung obstruction are signs of cystic fibrosis. Therapy for cystic fibrosis is limited to the improvement of the airway mokus, recovery of infections maintained with antibiotics, improve physical health and nutrition of patients